PENERAPAN PPDB ONLINE SISTEM ZONASI KOTA SURABAYA DALAM PERSPEKTIF GOOD GOVERNANCE - Fierda Nurany (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2022)
The aims of the online-based PPDB zoning system is to analyze the application of the Surabaya City zoning system online in the perspective of good governance, to find out the positive and negative impacts of implementing the online zoning system PPDB. The government in the distribution of education one of which is issuing new policies in accepting new student admissions through Minister of Education and Culture Regulations. The zoning system is part of the school reform effort to improve the quality of education in Indonesia. According to Mardiasmo there are principles of good government governance, as follows: Accountability (Accountability), Transparency (Transparancy)), Democracy (Democration), Rule of Law. The benefits of PPDB online Zoning System are that it is more efficient, makes it easier for the community, improving the quality of education and there are also positive and negative impacts in the application In this study, implementing that the process of Implementing New Student Admissions (PPDB) conducted online Zoning in the city of Surabaya has been considered successful in efforts to express access and quality of education.